Implementasi Ta’arudul Al ‘Am Wal Khas Menurut Mazhab Hanafi dan Mazhab Syafi’i dalam Hukum Islam - St. Halimang (STAIFAS-Press, 2020)
The discursus about Islamic law about continuing to see the importance of Al-Ta'ārud occurred because of the inadedience of the mujtaid knowing the will of as-Shari' in knowing the nature of nașș. There is no indeed contradiction in nașș because it means al-ta'ārud weakness, whereas Allah almighty is an omnilime substance and far from the nature of opposition, in addition that the owner of the law is only one god almighty, so there can be no contradiction. If there is, then the opposition is not an insanity opposition. When they came across two contradictory arguments, all the scholars agreed that it was not an insanity opposition. However, if the hel occurs, then it is mandatory for the law to be discussed and sought a solution. In terms of completing al-ta'ārud al-'ām wa al-khāș the scholars of the Hanafi and Shafi'i sects offer many methods or solutions sequentially.